Preparation method of amorphous magnetic powder core with high saturation flux density

By using technical means such as composite coating and pressing heat treatment in the preparation process of amorphous magnetic powder core, the problem of low saturation magnetic induction strength of amorphous magnetic powder core is solved, and the effect of high saturation magnetic induction strength and low loss is achieved, which is suitable for areas with high magnetic performance requirements.

CN119764040APending Publication Date: 2025-04-04ANHUI ONE MAGNET ELECTRONIC CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411994094.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The saturated magnetic induction strength of the amorphous magnetic powder core is low, making it difficult to meet the needs of high saturated magnetic induction strength and low loss at the same time.

Method used

The processes of smelting, atomization powder making, argon drying, ball milling, particle size grading, composite coating and pressing heat treatment are adopted. The mixed inert gas of nitrogen and argon are used for atomization treatment, and the boric acid-chromic acid composite passivator and polyimide-silicon composite adhesive are used for coating and bonding treatment, and stress annealing heat treatment is carried out.

Benefits of technology

It significantly improves the saturated magnetic induction strength of the amorphous magnetic powder core and reduces losses. It is suitable for areas with higher requirements for magnetic performance, while optimizing production efficiency and product quality, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764040A_ABST
    Figure CN119764040A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an amorphous magnetic powder core with high saturation flux density, and belongs to the technical field of soft magnetic materials. The method comprises the steps of smelting, gas atomization powder preparation, drying, ball milling, grain size distribution, composite coating, pressing heat treatment and the like. In the gas atomization powder preparation process, mixed inert gas is used for atomization treatment, and the mixed inert gas is nitrogen and argon; in the composite coating process, a boric acid-chromic acid composite passivating agent is used for coating treatment; in the pressing heat treatment process, a polyimide-silicon resin composite binder is firstly used, and then pressing is carried out. According to the method, the amorphous magnetic powder core with high saturation flux density and low loss is prepared by optimizing the raw material ratio, the composition of the coating agent and the binder and the heat treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a method for preparing an amorphous magnetic powder core with high saturation magnetic induction intensity. Background Art

[0002] Amorphous magnetic powder core is a new type of soft magnetic material with advantages such as high saturation magnetic induction intensity, low loss, and good temperature stability. It is widely used in the fields of electronics, electrical, and information. With the continuous improvement of my country's scientific and technological level, the market prospect of amorphous magnetic powder core is broad and has gradually become a hot spot of industry attention.

[0003] Amorphous magnetic powder cores originated in the United States in the 1970s, and my country began to study them in the 1980s. Amorphous magnetic powder cores are mainly composed of amorphous alloy powder, insulating medium and binder. Amorphous alloy powder is prepared by rapid solidification technology and has an atomic-level microstructure, which gives it excellent magnetic properties. The insulating medium is used to improve the insulation performance of the magnetic powder core and reduce eddy current losses. The binder plays a role in fixing the amorphous alloy powder and the insulating medium.

[0004] At present, the amorphous magnetic powder core industry is developing rapidly, with a wide variety of products and continuously improving performance. In terms of preparation technology, there are mainly melt spinning method, gas atomization method, etc. Among them, the melt spinning method has become the mainstream preparation method due to its high production efficiency and low cost. In the application field, amorphous magnetic powder cores have been successfully used in components such as transformers, inductors, filters, as well as new energy fields such as new energy vehicles, wind power generation, photovoltaic power generation, etc.

[0005] However, the amorphous magnetic powder core industry still faces some challenges, such as low saturation magnetic induction intensity and large high-frequency losses. It is difficult to achieve good thermal stability while having good saturation magnetic induction intensity and low losses. For example, patent CN116435085A provides a method for preparing low-loss, high-performance iron-based amorphous magnetic powder cores. By coating a layer of super-hydrophobic nano-SiO2 insulating layer on the surface of the magnetic powder, the eddy current loss at high frequency is effectively reduced and the DC bias performance is improved. The method is simple in process and low in cost, and optimizes the material selection and coating process, making it more suitable for coating treatment. However, the preparation method reduces the pressing density of the magnetic powder core, thereby affecting its magnetic permeability and saturation magnetic induction intensity. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing an amorphous magnetic powder core with high saturation magnetic flux density, so as to solve the problem that the saturation magnetic flux density of the amorphous magnetic powder core is low.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing an amorphous magnetic powder core with high saturation magnetic induction intensity comprises the following steps:

[0009] Melting, gas atomization powder making, argon drying, ball milling, particle size distribution, composite coating and pressing heat treatment;

[0010] In the process of gas atomization powder making, a mixed inert gas is used for atomization treatment, and the mixed inert gas is nitrogen and argon; in the process of composite coating, a boric acid-chromic acid composite passivator is used for coating treatment; in the process of pressing heat treatment, a polyimide-silicone resin composite binder is first used, and then pressing is performed.

[0011] Furthermore, the specific steps of the smelting are:

[0012] The raw materials are melted in a vacuum induction melting furnace at a melting temperature of 1500-1550° C. to obtain an alloy solution; the raw materials are FeSiBNi alloy, and the components of the raw materials include: Si: 5-10%, Al: 1-5%, B: 3-5%, Co: 5-15%, Ni: 4-8%, Cr: 0.5-5%, P: 0.5-2%, and the remainder of Fe and a small amount of impurities that are difficult to remove.

[0013] Furthermore, the specific steps of the aerosol powder making are:

[0014] The alloy solution is atomized in an atmosphere of a mixed inert gas with a mass ratio of nitrogen to argon of 1:1 and a gas pressure of 3.5-5.5 MPa to obtain an amorphous alloy powder.

[0015] Furthermore, the specific steps of the argon drying are:

[0016] The amorphous alloy powder is added into a dryer for drying. Argon is introduced as a protective gas during the drying process. The drying temperature is 150-180° C. and the drying time is 3-4 hours to obtain dry amorphous alloy powder.

[0017] Furthermore, the specific steps of the ball milling are:

[0018] The dried amorphous alloy powder is ball-milled for 2-3 hours to obtain flattened amorphous alloy powder.

[0019] Furthermore, the specific steps of the particle size grading are:

[0020] The flattened amorphous alloy powder is subjected to particle size grading to obtain a finished amorphous alloy powder with a median particle size D50 of 18-24 μm, D10 of 8-10 μm, and D90 of 32-38 μm.

[0021] Furthermore, the specific steps of the composite coating are:

[0022] Add boric acid-chromic acid composite passivator to the finished amorphous alloy powder for coating treatment, stir for 30-45 minutes, place in 130-150° C. environment and dry for 120-150 minutes to obtain coated amorphous alloy powder.

[0023] Furthermore, the specific steps of the pressing heat treatment are:

[0024] A polyimide-silicone resin composite binder is added to the coated amorphous alloy powder, ultrasonic stirring is used for 20-30 minutes, the powder is dried at 120-130°C for 60-80 minutes, pressed at a pressure of 1600-1800 MPa, and placed in a vacuum tube furnace for stress annealing heat treatment at 620-650°C for 6-8 hours to prepare an amorphous magnetic powder core.

[0025] Furthermore, in the boric acid-chromic acid composite passivator, the mass ratio of boric acid to chromic acid is 3-6:4-7; the boric acid-chromic acid composite passivator accounts for 0.4-0.8% of the mass of the finished amorphous alloy powder; the boric acid-chromic acid composite passivator uses acetone as a diluent, and the amount of acetone used is 6-10% of the mass of the finished amorphous alloy powder.

[0026] Furthermore, in the polyimide-silicone resin composite binder, the mass ratio of polyimide to silicone resin is 2-4:6-8; the polyimide-silicone resin composite binder accounts for 1-3% of the mass of the amorphous alloy powder after coating treatment; the silicone resin is 600 silicone resin, and the polyimide-silicone resin composite binder uses acetone as a diluent, and the amount of acetone used is 5-8% of the mass of the amorphous alloy powder after coating treatment.

[0027] Beneficial effects of the present invention:

[0028] (1) The amorphous magnetic powder core prepared by the present invention has a higher saturation magnetic induction intensity and can be applied in fields with higher requirements on magnetic properties.

[0029] (2) The present invention prepares an amorphous magnetic powder core with high saturation magnetic induction intensity and low loss by optimizing the composition of the coating agent and the binder, as well as the heat treatment process; by optimizing the preparation process, the production efficiency and product quality are improved, and the production cost is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be further described below in conjunction with the accompanying drawings.

[0031] Figure 1 This is a process flow chart for preparing the amorphous magnetic powder core of the present invention;

[0032] Figure 2 3 is a particle size distribution diagram of the amorphous magnetic powder core prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a method for preparing an amorphous magnetic powder core with high saturation magnetic induction intensity, comprising: Figure 1 The following steps are shown in the process flow chart of the amorphous magnetic powder core preparation process of the present invention:

[0036] S1. Melting: Melting the raw material, i.e., FeSiBNi alloy, in a vacuum induction melting furnace at a melting temperature of 1540° C. according to a mass ratio of Si: 5.5%, Al: 4%, B: 3%, Co: 9%, Ni: 6%, Cr: 4%, P: 1%, and the remainder of Fe and a small amount of impurities that are difficult to remove, to obtain an alloy solution;

[0037] S2. Gas atomization powder making: atomizing the alloy solution in a mixed inert gas atmosphere with a mass ratio of nitrogen to argon of 1:1 at a gas pressure of 4.5 MPa to obtain amorphous alloy powder;

[0038] S3, argon drying: adding the amorphous alloy powder to a dryer for drying, introducing argon as a protective gas during the drying process, the drying temperature is 160° C., the drying time is 3 h, and dry amorphous alloy powder is obtained;

[0039] S4, ball milling: ball milling the dried amorphous alloy powder for 3 hours to obtain flattened amorphous alloy powder;

[0040] S5. Particle size grading: performing particle size grading on the flattened amorphous alloy powder to obtain a finished amorphous alloy powder having a median particle size D50 of 21 μm, D10 of 9 μm, and D90 of 34 μm;

[0041] S6, composite coating: add 0.4g of boric acid-chromic acid composite passivator to 100g of finished amorphous alloy powder for coating treatment, wherein the mass ratio of boric acid to chromic acid in the boric acid-chromic acid composite passivator is 4:6, and weigh 8g of acetone as a diluent, stir for 30min, and dry at 150°C for 120min to obtain amorphous alloy powder after coating treatment;

[0042] S7, pressing heat treatment: add 2.5g of polyimide-silicone resin composite binder to 100g of the coated amorphous alloy powder, the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 2:8, and weigh 6g of acetone as a diluent, use ultrasonic stirring for 30min, place it in an environment of 120℃ and dry it for 60min, press it under a pressure of 1600MPa, and place it in a vacuum tube furnace at 620℃ for stress annealing heat treatment for 8h to prepare an amorphous magnetic powder core; Figure 2 3 is a particle size distribution diagram of the amorphous magnetic powder core prepared in Example 1.

[0043] Example 2

[0044] Compared with Example 1, the present embodiment is different in that step S6 "adding 0.4g of boric acid-chromic acid composite passivator to 100g of finished amorphous alloy powder for coating treatment, the mass ratio of boric acid to chromic acid in the boric acid-chromic acid composite passivator is 4:6, and weighing 8g of acetone as a diluent, stirring for 30min, and drying at 150°C for 120min to obtain coated amorphous alloy powder" is changed to "adding 0.4g of boric acid-chromic acid composite passivator to 100g of finished amorphous alloy powder for coating treatment, the mass ratio of boric acid to chromic acid in the boric acid-chromic acid composite passivator is 6:4, and weighing 8g of acetone as a diluent, stirring for 30min, and drying at 150°C for 120min to obtain coated amorphous alloy powder"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0045] Example 3

[0046] Compared with Example 1, the present embodiment differs in that step S7 "adding 2.5 g of polyimide-silicone resin composite binder to 100 g of coated amorphous alloy powder, wherein the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 2:8, and weighing 6 g of acetone as a diluent, using ultrasonic stirring for 30 min, drying at 120° C. for 60 min, pressing at a pressure of 1600 MPa, and placing in a vacuum tube furnace for stress annealing heat treatment at 620° C. for 8 h, to prepare an amorphous magnetic powder core" The method is changed to “add 2.5 g of a polyimide-silicone resin composite binder to 100 g of the coated amorphous alloy powder, wherein the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 4:6, and 6 g of acetone is weighed as a diluent, and ultrasonic stirring is used for 30 min, and the mixture is dried at 120°C for 60 min, pressed at a pressure of 1600 MPa, and placed in a vacuum tube furnace for stress destressing annealing heat treatment at 620°C for 8 h to obtain an amorphous magnetic powder core”; the remaining raw materials and preparation process remain the same as those in Example 1.

[0047] Example 4

[0048] Compared with Example 3, the present embodiment differs in that step S7 "adding 2.5 g of polyimide-silicone resin composite binder to 100 g of the coated amorphous alloy powder, wherein the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 4:6, and weighing 6 g of acetone as a diluent, using ultrasonic stirring for 30 min, drying at 120° C. for 60 min, pressing at a pressure of 1600 MPa, and placing in a vacuum tube furnace for stress annealing heat treatment at 620° C. for 8 h, to prepare an amorphous magnetic powder core" The method is changed to “add 1.5 g of a polyimide-silicone resin composite binder to 100 g of the coated amorphous alloy powder, wherein the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 4:6, and 6 g of acetone is weighed as a diluent, and ultrasonic stirring is used for 30 min, and the mixture is dried at 120°C for 60 min, pressed at a pressure of 1600 MPa, and placed in a vacuum tube furnace for stress destressing annealing heat treatment at 620°C for 8 h to obtain an amorphous magnetic powder core”; the remaining raw materials and preparation process remain the same as those in Example 3.

[0049] Example 5

[0050] Compared with Example 3, the present embodiment is different in that step S6 "adding 0.4g of boric acid-chromic acid composite passivator to 100g of finished amorphous alloy powder for coating treatment, the mass ratio of boric acid to chromic acid in the boric acid-chromic acid composite passivator is 4:6, and weighing 8g of acetone as a diluent, stirring for 30min, and drying at 150°C for 120min to obtain coated amorphous alloy powder" is changed to "adding 0.8g of boric acid-chromic acid composite passivator to 100g of finished amorphous alloy powder for coating treatment, the mass ratio of boric acid to chromic acid in the boric acid-chromic acid composite passivator is 4:6, and weighing 8g of acetone as a diluent, stirring for 30min, and drying at 150°C for 120min to obtain coated amorphous alloy powder"; the remaining raw materials and preparation process remain the same as those in Example 3.

[0051] Example 6

[0052] Compared with Example 3, the present embodiment differs in that step S7 "adding 2.5 g of polyimide-silicone resin composite binder to 100 g of the coated amorphous alloy powder, wherein the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 4:6, and weighing 6 g of acetone as a diluent, using ultrasonic stirring for 30 min, drying at 120° C. for 60 min, pressing at a pressure of 1600 MPa, and placing in a vacuum tube furnace for stress annealing heat treatment at 620° C. for 8 h, to prepare an amorphous magnetic powder core" The method is changed to “add 2.5 g of a polyimide-silicone resin composite binder to 100 g of the coated amorphous alloy powder, wherein the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 4:6, and 6 g of acetone is weighed as a diluent, and ultrasonic stirring is used for 30 min, and the mixture is dried at 120°C for 60 min, pressed at a pressure of 1600 MPa, and placed in a vacuum tube furnace for stress destressing annealing heat treatment at 640°C for 8 h to obtain an amorphous magnetic powder core”; the remaining raw materials and preparation process remain the same as those in Example 3.

[0053] Comparative Example 1

[0054] Compared with Example 3, the difference between this comparative example and Example 3 is that step S6 "adding 0.4g of boric acid-chromic acid composite passivator to 100g of finished amorphous alloy powder for coating treatment, the mass ratio of boric acid to chromic acid in the boric acid-chromic acid composite passivator is 4:6, and weighing 8g of acetone as a diluent, stirring for 30min, and drying at 150°C for 120min to obtain amorphous alloy powder after coating treatment" is changed to "adding 0.4g of phosphoric acid to 100g of finished amorphous alloy powder for coating treatment, and weighing 8g of acetone as a diluent, stirring for 30min, and drying at 150°C for 120min to obtain amorphous alloy powder after coating treatment"; the remaining raw materials and preparation process remain the same as those in Example 3.

[0055] Comparative Example 2

[0056] Compared with Example 3, the difference between this comparative example and Example 3 is that the step S1 "melting the raw materials, i.e., FeSiBNi alloy, in a mass ratio of Si: 5.5%, Al: 4%, B: 3%, Co: 9%, Ni: 6%, Cr: 4%, P: 1%, and the balance Fe and a small amount of impurities that are difficult to remove, and melting them in a vacuum induction melting furnace at a melting temperature of 1540°C to obtain an alloy solution" is changed to "melting the raw materials, i.e., FeSiBNi alloy, in a mass ratio of Si: 8%, Al: 4%, B: 3%, Co: 4%, Ni: 6%, Cr: 4%, P: 0.01%, and the balance Fe and a small amount of impurities that are difficult to remove, and melting them in a vacuum induction melting furnace at a melting temperature of 1540°C to obtain an alloy solution"; the remaining raw materials and preparation process remain the same as those in Example 3.

[0057] Comparative Example 3

[0058] Compared with Example 3, the difference between this comparative example and Example 3 is that step S7 "adding 2.5g of polyimide-silicone resin composite binder to 100g of the coated amorphous alloy powder, the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 4:6, and weighing 6g of acetone as a diluent, using ultrasonic stirring for 30min, drying at 120℃ for 60min, pressing at a pressure of 1600MPa, and placing in a vacuum tube furnace for stress annealing heat treatment at 620℃ for 8h to prepare an amorphous magnetic powder core" The method is changed to “add 2.5 g of a polyimide-silicone resin composite binder to 100 g of the coated amorphous alloy powder, wherein the mass ratio of polyimide to 600 silicone resin in the polyimide-silicone resin composite binder is 4:6, and 6 g of acetone is weighed as a diluent, and ultrasonic stirring is used for 30 min, and the mixture is dried at 120°C for 60 min, pressed at a pressure of 1000 MPa, and placed in a vacuum tube furnace for stress annealing heat treatment at 620°C for 8 h to obtain an amorphous magnetic powder core”; the remaining raw materials and preparation process remain the same as those in Example 3.

[0059] The amorphous magnetic powder cores prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to performance tests to test their saturation magnetic induction intensity and loss. The MATS magnetic material automatic measurement system V7.0 of Hunan Lianzhong Technology Co., Ltd. was used for testing. The results are shown in Table 1:

[0060] Table 1

[0061] project Saturation magnetic induction intensity (T) Loss (W / kg) Example 1 1.42 6.5 Example 2 1.41 6.6 Example 3 1.43 6.3 Example 4 1.42 6.4 Example 5 1.41 6.6 Example 6 1.41 6.4 Comparative Example 1 1.34 6.9 Comparative Example 2 1.32 7.0 Comparative Example 3 1.35 6.9

[0062] It can be seen from Table 1 that the saturation magnetic induction intensity of the amorphous magnetic powder cores prepared in Examples 1 to 6 is maintained between 1.41 and 1.43 T, and the loss is between 6.3 and 6.6 W / kg, showing higher saturation magnetic induction intensity and lower loss.

[0063] Compared with Example 1, Comparative Example 1 uses "phosphoric acid" instead of "boric acid-chromic acid composite passivator" to coat the finished amorphous alloy powder, and the saturation magnetic induction intensity of the obtained amorphous magnetic powder core is lower and the loss is higher; Compared with Example 1, Comparative Example 2 changes the raw material ratio, and the saturation magnetic induction intensity of the obtained amorphous magnetic powder core is also lower, and the loss is higher; Compared with Example 1, Comparative Example 3 changes the pressing pressure, and the saturation magnetic induction intensity of the obtained amorphous magnetic powder core is also lower, and the loss is higher; This shows that the technical scheme of the present invention has a significant effect on improving the performance of amorphous magnetic powder cores.

[0064] The saturation magnetic induction intensity of the amorphous magnetic powder cores prepared in Examples 1 to 6 is higher than that of Comparative Examples 1 to 3, indicating that the technical solution of the present invention can effectively improve the magnetic properties of the amorphous magnetic powder core, making it suitable for fields with higher requirements on magnetic properties.

[0065] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an amorphous magnetic powder core with high saturation magnetic induction intensity, characterized in that: The steps include: Melting, gas atomization powder making, argon drying, ball milling, particle size distribution, composite coating and pressing heat treatment; In the process of gas atomization powder making, a mixed inert gas is used for atomization treatment, and the mixed inert gas is nitrogen and argon; in the process of composite coating, a boric acid-chromic acid composite passivator is used for coating treatment; in the process of pressing heat treatment, a polyimide-silicone resin composite binder is first used, and then pressing is performed.

2. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of the smelting are: The raw materials are melted in a vacuum induction melting furnace at a melting temperature of 1500-1550° C. to obtain an alloy solution; The raw material is FeSiBNi alloy, and the components of the raw material include: Si: 5-10%, Al: 1-5%, B: 3-5%, Co: 5-15%, Ni: 4-8%, Cr: 0.5-5%, P: 0.5-2%, and the balance of Fe and a small amount of impurities that are difficult to remove.

3. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of the aerosol powder making are: The alloy solution is atomized in an atmosphere of a mixed inert gas with a mass ratio of nitrogen to argon of 1:1 and a gas pressure of 3.5-5.5 MPa to obtain an amorphous alloy powder.

4. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of the argon drying are: The amorphous alloy powder is added into a dryer for drying. Argon is introduced as a protective gas during the drying process. The drying temperature is 150-180° C. and the drying time is 3-4 hours to obtain dry amorphous alloy powder.

5. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of the ball milling are: The dried amorphous alloy powder is ball-milled for 2-3 hours to obtain flattened amorphous alloy powder.

6. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of the particle size grading are: The flattened amorphous alloy powder is subjected to particle size grading to obtain a finished amorphous alloy powder with a median particle size D50 of 18-24 μm, D10 of 8-10 μm, and D90 of 32-38 μm.

7. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of the composite coating are: Add boric acid-chromic acid composite passivator to the finished amorphous alloy powder for coating treatment, stir for 30-45 minutes, place in 130-150° C. environment and dry for 120-150 minutes to obtain coated amorphous alloy powder.

8. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 1, characterized in that: The specific steps of the pressing heat treatment are: A polyimide-silicone resin composite binder is added to the coated amorphous alloy powder, ultrasonic stirring is used for 20-30 minutes, the powder is dried at 120-130°C for 60-80 minutes, pressed at a pressure of 1600-1800 MPa, and placed in a vacuum tube furnace for stress annealing heat treatment at 620-650°C for 6-8 hours to prepare an amorphous magnetic powder core.

9. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 7, characterized in that: In the boric acid-chromic acid composite passivator, the mass ratio of boric acid to chromic acid is 3-6:4-7; the boric acid-chromic acid composite passivator accounts for 0.4-0.8% of the mass of the finished amorphous alloy powder; the boric acid-chromic acid composite passivator uses acetone as a diluent, and the amount of acetone used is 6-10% of the mass of the finished amorphous alloy powder.

10. The method for preparing a high saturation magnetic induction intensity amorphous magnetic powder core according to claim 8, characterized in that: In the polyimide-silicone resin composite binder, the mass ratio of polyimide to silicone resin is 2-4:6-8; the polyimide-silicone resin composite binder accounts for 1-3% of the mass of the amorphous alloy powder after coating treatment; the silicone resin is 600 silicone resin, and the polyimide-silicone resin composite binder uses acetone as a diluent, and the amount of acetone used is 5-8% of the mass of the amorphous alloy powder after coating treatment.

Citation Information

Patent Citations

  • Amorphous soft magnetic alloy and inductance component using the same

    CN101572153A

  • High saturation magnetic induction intensity iron-based amorphous soft magnetic composite material and manufacturing method thereof

    CN104036904A

  • Method for preparing magnetic powder core from amorphous nanocrystalline

    CN108172388A

  • Modified binder and method for preparing soft magnetic composite material by using same

    CN111883328A

  • Magnetic core powder, preparation method thereof and inductor

    CN113380489A